Eugenol: A novel therapeutic agent for the inhibition of Candida species infection - Didehdar, Mojtaba; Chegini, Zahra; Shariati, Aref (Frontiers in Pharmacology, 2022)
The high occurrence and mortality rates related to candidiasis emphasize the urgent need to introduce new therapeutic approaches to treat this infection. Eugenol, the main phenolic component of Clove and Cinnamomum essential oil, has been used to inhibit growth and different virulence factors of Candida, including strains with decreased susceptibility to antifungals, particularly fluconazole. The results showed that this compound could bind to Candida membrane and decrease ergosterol biosynthesis, consequently leading to cell wall and membrane damage. Additionally, eugenol not only reduced germ tube formation, which reduces nutrient absorption from host tissues, but it also increased the levels of lipid peroxidation and reactive oxygen species, which induces oxidative stress and causes high permeability in the fungal cell membrane. Eugenol inhibited Candida cells’ adhesion capacity; additionally, this compound inhibited the formation of biofilms and eliminated established Candida biofilms on a variety of surfaces. Furthermore, by disrupting fungal cell integrity, eugenol could boost the entry of the antifungal drugs into the Candida cell, improving treatment efficacy. Therefore, eugenol could be used in the clinical management of various presentations of candidiasis, especially mucocutaneous presentations such as oral and vulvovaginal infections. However, further investigations, including in vivo and animal studies, toxicology studies and clinical trials, as well as molecular analysis, are needed to improve formulations and develop novel antifungal agents based on eugenol.